2021
DOI: 10.3389/fmicb.2021.702725
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Resistance in Salmonella Typhimurium and Its Association With Disinfectant and Antibiotic Resistance

Abstract: Metals are widely used in animal feed for their growth-stimulating and antimicrobial effects, yet their use may potentially promote the proliferation of antibiotic resistance through co-selection. We studied the prevalence and associations of metal, antibiotic, and disinfectant resistances of 300 Salmonella Typhimurium isolates from pig meat, pig manure, chicken meat, poultry manure, and human stool from Sichuan, China. Seventy four percent of the 300 Salmonella Typhimurium isolates were considered resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…which may be attributed to the fact that the temperature of grilling is not sufficient to kill micro-organisms, besides it receives more handling during preparation. This result was consistent with Abd El-Tawab et al ( 2015) and Mustafa et al (2021) who found that 10.9% and 10% of the examined chicken meat were positive for Salmonella, respectively. Other studies registered higher incidences of the organism as those conducted by Hassanin et al (2014) (22.2%) and Saad et al (2015) (15%).…”
Section: Phylogenetic Analysissupporting
confidence: 92%
“…which may be attributed to the fact that the temperature of grilling is not sufficient to kill micro-organisms, besides it receives more handling during preparation. This result was consistent with Abd El-Tawab et al ( 2015) and Mustafa et al (2021) who found that 10.9% and 10% of the examined chicken meat were positive for Salmonella, respectively. Other studies registered higher incidences of the organism as those conducted by Hassanin et al (2014) (22.2%) and Saad et al (2015) (15%).…”
Section: Phylogenetic Analysissupporting
confidence: 92%
“…The presence of possible direct or indirect contact between susceptible species (humans and animals) of zoonotic pathogens is a sensitive point on which it is prudent to intervene by means of training, information, and prevention measures [ 40 , 41 ]. For instance, captive animals may be trained for different purposes, i.e., to interact with the public for educational demonstrations, for husbandry purposes, or for non-invasive medical procedures to be performed in non-sedated animals (e.g., nasal swabs, blood samples): these practices are contemplated to ensure more efficient and less impactful health control on the captive animal population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of metal tolerant foodborne pathogens has been reported by multiple studies. It is accepted that an antimicrobial co-resistance and cross-resistance phenomena (resistance borne by adjacent genetic markers in mobile genome such as integrons and the multiple-resistance physiological mechanisms related to one genetic marker, respectively) may be screened by a toxic metal tolerance [ 36 , 37 , 38 ]. Nonetheless, the lack of technical standards for such experimental designs hinders a data comparison.…”
Section: Discussionmentioning
confidence: 99%